Crushing characteristics of bionic thin-walled tubes inspired by bamboo and beetle forewing. Issue 14 (1st June 2022) - Zhang, Linwei; Zhong, Yong; Tan, Wenxiao; Gong, Chao; Hu, Yong; Bai, Zhonghao
Abstract: Bionic structures have garnered considerable attention due to their superior energy absorption capacity and light weight. This study proposes a group of bionic thin-walled tubes inspired by the microstructure of bamboo and beetle forewing. Experimental testing is conducted to validate the finite element model of bionic thin-walled tubes. The crushing performance of bionic thin-walled tubes and traditional thin-walled tubes is compared under the same weight. The bionic thin-walled tube with excellent crashing performance is further determined, that is, B-9-W. Then, parametric studies of the B-9-W tube are performed to reveal the effect of geometric parameters on crashworthiness characteristics. Finally, multi-objective optimization is carried out to seek the optimal design of B-9-W. Results show that, compared with two traditional thin-walled tubes, the specific energy absorption of the optimized B-9-W increases by 44.124% and 125.058%, respectively.